The Link between Workplace Safety Climate and Job Performance among Nursing Staff: A Correlational Study - Zineelabdine Salih Mahdi; Selman Hussain Faris (Kufa Journal for Nursing Sciences)
Background: Workplace safety climate and job performance are closely related. A positive safety climate is associated with better job performance, particularly in health care settings.